Development of Slice Test Device for Testing Natural Rubber Composites Similarity with Incision Cadaver on Surgical Process - Riri Murniati; Muhammad Nuraliffudin Saputra; Arini Fitria Gunawan; Nanda Novita (Jurnal Ilmu Fisika, 2023)
This research has developed the slice test device to test natural rubber composites made of magnetically modified natural zeolite on nanosilica-reinforced natural rubber composites. We tested the sample similarity with incision cadavers in surgical practice with mechanical characteristics like human tissue. Natural rubber was used as a primary component in the production of synthetic human tissue. The natural rubber was blended with magnetic particle nanosilica, an alternative filler that mixes nanosilica, natural zeolite, and magnetite. This project used several materials formulas to give synthetic human tissue the desired mechanical qualities and incision test characteristics. We used technical specifications rubber (TSR) SIR 20 with nanosilica reinforced fillers and Titanate coupling agent (TCA) as filler and elastomer binders. Samples were characterized using Universal Testing Machine and then tested with the incision test equipment specially designed by the team. Mechanical characteristics of different human body part tissue were compared to the control samples and had similar mechanical characteristics with internal human tissue characteristics. It was found that nanosilica fillers combined with magnetically modified zeolites and titanate coupling agents are potentially applicable for synthetic muscle replacement cadavers with a custom formula.